Penerapan 5R Area Produksi Paving Blok di PT. Duta Beton Mandiri Purwosari - Husna, Siti Misbahul; Pusakaningwati, Ayik (Ikatan Da'i Indonesia, 2024)
Duta Beton Mandiri is a Duta Bangsa Group company based in Pasuruan Regency. PT. Duta Beton Mandiri is a manufacturing company that was founded in 2008 and operates in the building materials or concrete industry. We implement 5R (Care, Neat, Clean, Diligent, Concise) and work safety (K3) at the PT paving stone production site. Duta Beton Mandiri is a strategic initiative to increase production efficiency while maintaining a safe and healthy work environment. The aim of this research is to evaluate the implementation of the 5R and K3 principles and to conduct an audit to determine compliance with applicable K3 standards. Research methods include direct observation of production sites, interviews with employees, and analysis of relevant materials. Research shows that implementing the 5R principles reduces waste and optimizes resource use. In addition, efforts to implement K3 have increased awareness of risk factors and reduced work accidents. However, there is still much room for improvement, especially in terms of increasing the use of personal protective equipment and machine maintenance.